Pengaruh Perbandingan Tepung Ubi Jalar Kuning (Ipomea Batatas L.) Dengan Tepung Kentang (Solanum Tuberosum) Dan Lama Pengeringan Terhadap Mutu Bubuk Sup Labu Kuning Instan - Br Tarigan, Pricillia Azhari Angelica; Ginting, Sentosa; Suhaidi, Ismed (Universitas Medan Area, 2023)
This research was conducted to determine the effect of the ratio of yellow sweet potato flour to potato starch and drying time on the quality of instant pumpkin soup. This study used a factorial Completely Randomized Design method with 2 factors, namely: the ratio of yellow sweet potato flour to potato starch (T): (50%:50% ; 60%:40% ; 70%:30% ; 80%:20 %) and drying time (L): (18 hours ; 21 hours ; 24 hours). The results showed that the ratio of yellow sweet potato flour to potato flour had a highly significant different effect on water content, protein content, fat content, crude fiber content, carbohydrate content, water absorption, organoleptic value of aroma, taste, texture, and organoleptic value of general acceptance. Drying time has a very significant effect on moisture content, fat content, protein content, crude fiber content, carbohydrate content, water absorption, color value (ohue), and texture organoleptic value. The interaction between the ratio of yellow sweet potato flour to potato starch and drying time had a highly significant different effect on the moisture content, carbohydrate content, and water absorption capacity of instant pumpkin soup powder.